Ácaros tetraniquídeos (prostigmata: tetranychidae) associados à soja no Rio Grande do Sul: ocorrência, identificação de espécies e efeito de cultivares e de plantas daninhas - Roggia, Samuel (2007)
The spider mite occurrence, on soybean (Glycine max (L.) Merril), is sporadic and associated whit dry periods. Recently, in continuous years, was reported mite outbreaks in soybean, in some sites of Rio Grande do Sul State. In this context two research was conducted, one in summer crop 2004/05 and other in 2005/06. The first was carried for study the mite occurrence and geographic distribution, on soybean, from some place of Rio Grande do Sul State. The second was conducted for study the effect of the two soybean cultivars and of some weed management systems on mite density and study their population dynamic on soybean. In summer crop 2004/05 was carried some mite samplings in soybean field at State. The mite species found, all beloung to the Tetranychidae family, are Mononychellus planki (McGregor), Tetranychus desertorum Banks, T. gigas Pritchard & Baker, T. ludeni Zacher and T. urticae Koch. Most of this species are well distributed in the diferents sampling regions of this study. From the results was made a species distribution map and a taxonomic key. In summer crop 2005/06, in Santa Maria, RS, 11 treatments was study. Its was constitute in two soybean cultivars, one transgenic glyphosato-tolerant and other non-transgenic, every one whit five weed management systems: (1) without management; (2) hand management; (3) herbicide bentazone + sethoxydim; (4) bentazone only; (5) sethoxydim only. The 11th treatment was the herbicide glyphosate sprayed on the transgenic soybean. The mite species found in this study are M. planki and T. gigas. The weed management systems is more determinant, on the spider mite population on soybean, than the soybean cultivar. The mite population presenteded inverse correlation whit weed infestation and weed density. The climatic fators determined the mite population flutuation and the population peak occured in the initial period of soybean pods development.